Memoirs - Leland, Charles Godfrey, 1824-1903 (Salt Lake City, UT : Project Gutenberg, 2007)
"Memoirs" by Charles Godfrey Leland is an autobiographical account written in the late 19th century. The book reflects on Leland's life experiences and memories, including his family background, childhood in Philadelphia, and his interactions with prominent figures of his time. The author aims to provide an intimate glimpse into his personal development and the society he lived in, showcasing a mix of historical events and personal anecdotes. At the start of the memoir, Leland explains the context of his writing and outlines his intent to capture the essence of his life experiences accurately. He recalls his birthplace and early life in Philadelphia, enriched by engaging experiences with influential figures like General Lafayette and memories tied to familial connections from the Revolutionary War. The narrative evolves through his various educational experiences, the cultural milieu of Philadelphia, and influences from both his parents and noteworthy personalities surrounding him. Leland's vivid recollections and reflections set the stage for a deeper exploration of his journey throughout the memoir. (This is an automatically generated summary.)
Release date is 2007-07-09
Transcribed from the 1894 London William Heinemann edition by David Price
Keywords: Authors, American -- 19th century -- Biography; Leland, Charles Godfrey, 1824-1903